Rowing applied session improving rowing performance and minimising injury - Smith, R.; Draper, C.; Ng, L.; Lardy, J.; Teissier, F.; Colloud, F.; Fohanno, V.; Nordez, A. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
Competitive rowing has been practiced for millennia as evidenced by Egyptian wall paintings from 2500 BC. Boats from the First Egyptian Dynasty were 25 m long and 2 m wide had 30 rowers. Rowing races were conducted in Ancient Greece as part of festivals and games (Virgil, 19 - 30 BC) and in Rome regattas were organized for entertainment. The complexity of rowing boats probably reached their peak with the Greek Triremes which had 170 rowers in three banks. Today, in the modern day Olympics, there are 14 different events from the single scull to the sweep eight with coxswain. Further, ergometer rowing is an international sport in its own right. Both on-water and ergometer rowing are activities that are enjoyed recreationally and as a form of fitness training. Whatever the motivation for involvement in rowing, an understanding of the mechanisms of performance and injury can deepen appreciation of the sport. Progress will be made towards optimizing performance and minimizing injury when the relevant determinants are known. They can be grouped by their association with the rower, boat, oar and environment.